(untitled) (Economic and Political Thought, 2010)
The article discusses the United Kingdom’s policy towards the first postwar integration initiatives of Western Europe and the United States. The initiators and authors of projects to unite Europe were various political organizations of Western Europe and the government of the United States. The United Kingdom was a world superpower at that time and because of various reasons it had to take an ambivalent stand on the issue of Western European integration. On account of the specificity of its international interests, which are thoroughly analyzed by the author, this state could not actively participate in the European integration trend. However, it was not in the British interest to sabotage the integration undertakings of the continental part of Western Europe either. In such circumstances, the United Kingdom forced through a policy of close co-operation between Western European countries as an alternative to integration ideas. Until 1954 the British policy towards continental integration initiatives can be described as very effective. The United Kingdom skillfully managed to hold up the use of post-war American aid to Europe as a form of stimulus for Western European integration (European Recovery Program – Marshall Plan). As a result of its policy, an authentically European parliamentary assembly, aimed at initiating and stimulating European integration process through grass-roots social pressure on governments (Resolution of the Hague Congress), did not take place. The political and diplomatic successes determined the British assessment of prospects for the European integration and British possibilities to influence the process of Western European unification. They made British politicians incorrectly – as it turned out – believe that the United Kingdom could successfully halt attempts of supranational integration by forcing through an idea of co-operation of sovereign states. After a few years there were no doubts that the assessment had been wrong. In this case traditional attitude towards international politics did badly in comparison with new realities, i.e. an innovative integration trend.